PELAKSANAAN WORKSHOP GURU ASYIK DAN MENYENANGKAN (GURAME) TERHADAP MOTIVASI DAN INOVASI GURU - Rahmah Zaqiyatul Munawaroh; Melyana Indiarsih (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2023)
Being an innovative and creative teacher certainly requires great motivation. In this case, teachers need the right intake of knowledge and coaching to instill a sense of motivation. Thus, workshops are conducted for teachers as the target audience to measure the extent of teacher motivation and innovation in creating fun and fun learning. At the workshop stage, activities focused on mentoring partner teachers and prospective PIAUD and PGMI teachers in understanding the concept of fun and fun teachers. The next stage is for researchers to provide digital interview sheets to workshop participants to fill in as evaluation material for workshop activities. The questions given were related to the extent of understanding of workshop participants in creating fun and fun learning through workshop activities. Research data in the form of qualitative data with qualitative data analysis of Miles & Huberman. The existence of motivation and innovation as an output of the implementation of this workshop is expected to be a lasting positive value for teachers in creating and implementing learning that not only delivers material to students but can implement fun and friendly learning for children